What's the rest of the question?
Answer:
(f⋅g)(x)=8x^2−2x−15
Step-by-step explanation:
To find the expression (f*g)(x), multiply f(x) into g(x) using the distribution property.
(f*g)(x) = (2x - 3)(4x + 5) = 8x² - 12x + 10x - 15 = 8x² - 2x - 15
Answer:
M (-3, -5/2)
N (3, -1)
Step-by-step explanation:
Solve the first equation for x.
4y = x − 7
x = 4y + 7
Substitute into the second equation.
x² + xy = 4 + 2y²
(4y + 7)² + (4y + 7)y = 4 + 2y²
Simplify.
16y² + 56y + 49 + 4y² + 7y = 4 + 2y²
18y² + 63y + 45 = 0
2y² + 7y + 5 = 0
Factor.
(y + 1) (2y + 5) = 0
y = -1 or -5/2
Plug back into the first equation to find x.
x = 4(-1) + 7 = 3
x = 4(-5/2) + 7 = -3
M (-3, -5/2)
N (3, -1)
H=3 because 27 divided by 9 is 3
Answer:
Step-by-step explanation:
What you do first is multiply -4 and -5 which gives you 20 (two negatives gives you a postitive answer.) Then add 18 which gives you 38.
Answer: 38